If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -4 = -8(x + -1) Reorder the terms: -4 + y = -8(x + -1) Reorder the terms: -4 + y = -8(-1 + x) -4 + y = (-1 * -8 + x * -8) -4 + y = (8 + -8x) Solving -4 + y = 8 + -8x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + y = 8 + 4 + -8x Combine like terms: -4 + 4 = 0 0 + y = 8 + 4 + -8x y = 8 + 4 + -8x Combine like terms: 8 + 4 = 12 y = 12 + -8x Simplifying y = 12 + -8x
| 3x^3+27x^2+9x=0 | | 5[10-(3+4)+1]=14 | | 5Xsquared=75 | | -10x+x= | | 9+5x=17+x | | -5x+150=3+0.05x^2 | | 10x^4-12xy-16y^4= | | -5(-2+n)=-35 | | 2x^2-10x+12x^2= | | 4x+3+2x=x-8 | | 2x^4-10x+12x^4= | | 12x^4-12x+12x^4= | | 8m-12=52 | | x*3.5=1.75 | | 10x^4-10x+10x^4= | | 10x^4-20x+16x^4= | | 10x^4-20x-16x^4= | | 2cosx=-0.9 | | 10x^2+5= | | 11x^2-16x-60=0 | | 10x^2+16= | | -2n+5(6-8n)=30-n | | 8y=20 | | (6w-3)(4-3w)= | | 9+3x+x^2=0 | | 10x^2+16y= | | 4x(x+6)=288 | | 10x^2+4xy+16y= | | 5x-6b=2x+10y | | 10x^2+10xy+16y= | | 10x^2+10xy+16= | | 10x^2+10xy+16y^2= |